The impact of the Ukrainian-Russian war on Russia’s position in Central Asia on the example of relations with Kazakhstan - Furmańczyk, Norbert (Boundaries and Spheres of Influence in Domestic Politics and International Relations, 2023)
The purpose of this paper is to show, using the method of content analysis and the historical method, how the war caused by Russia on February 24, 2022 in Ukraine affected its position in Central Asia on the basis of the current relations of the Russian state with Kazakhstan. Since the times of tsarist Russia, Kazakhstan has been under its strong pressure, which increased during the times of the Soviet Union, when Kazakhstan became one of the union republics. After the collapse of the USSR, relations with Russia remained strong thanks to the long-term president of Kazakhstan, Nursultan Nazarbayev, who at the same time tried to build a Kazakh national identity. Over the years, one could notice smaller or larger problems in relations with Russia, but only now can one notice a significant decrease in Russian influence in Kazakhstan, which will affect the entire area of Central Asia. The main question remains whether the ineffective Russian campaign in Ukraine is the reason for the removal of the Kazakh state from Russia or is it caused by China's increasing influence on Kazakhstan? In order to answer this question, he will analyse both Russia's relations with Kazakhstan during the war with Ukraine and China's influence on these relations.